A multi-country analysis of informal caregiving due to others' drinking. (2nd November 2022) - Jiang, Heng; Laslett, Anne-Marie; Kuntsche, Sandra; Callinan, Sarah; Waleewong, Orratai; Room, Robin
Abstract: The burden of caring for drinkers is seldom articulated as a social concern, or integrated in service planning or alcohol policy. This study aims to examine prevalence and predictors of informal caregiving due to others' drinking cross-nationally by surveying 20, 728 respondents (18–64 years) in 11 countries. The outcome variable was respondent-reported informal caregiving due to others' drinking, analysed by socio-demographic factors and drinking pattern using logistic regression and meta-analysis. Estimated overall prevalence of informal caregiving due to others' drinking ranged from 9% in Nigeria to 47% in Thailand. In most countries, females reported a higher rate than males of caring for children and other dependents, but males reported a higher rate of driving family or friends somewhere or picking them up. Logistic regression analysis found differences between high-income countries and low- and middle-income countries in the relationship of caregiving with employment and household composition. Respondent's own drinking was positively correlated with the prevalence of caregiving in 10 out of 11 countries. In general, younger adults and those who are themselves risky drinkers are more likely to have had caring responsibilities. Although problematic drinking is concentrated in specific subpopulations, the burden of care for others' drinking extends widely across the population.